Lammproduktion på nio ekologiska gårdar i västra Sverige - Larsson, Karin (SLU/Dept. of Animal Environment and Health (until 231231), 2005)
The purpose with this study was to analyze the possibilities to produce organic lambs and to hihglight the most common difficulties in such a production system. A description of current organic and conventional lamb production systems was conducted, both from Sweden and from some other countries.